Implementation of Online Marketing Strategies Using Social Media For SME Martabak Bangka Sungai Liat Batam - Tasya Tasya; Edy Yulianto Putra (ConCEPt - Conference on Community Engagement Project, 2023)
During the process of working on this activity that had been approved, the practicioner realized that so far the owners of the Martabak Bangka Sungai Liat SME had only promoted their SME through manual method, which is from mouth to mouth. Therefore the practicioner concluded that the owner of the Martabak Bangka Sungai Liat SME doesn't yet have a social media account to promote their business. In this activity report, practicioner use social media promotion methods to help introduce Martabak Bangka Sungai Liat SME to wider community. The results of the project were shown in the form of Instagram, Facebook and Whatsapp Business social media accounts. The outputs produced by the practicioner through working on this activity report have been received and used by the owner of the Martabak Bangka Sungai Liat SME.